Sequence analysis and function of mosquito aeCCC2 and Drosophila Ncc83 orthologs. (April 2022) - Duong, Phu C.; McCabe, Tobias C.; Riley, Grace F.; Holmes, Heather L.; Piermarini, Peter M.; Romero, Michael F.; Gillen, Christopher M.
Abstract: Dipteran insects have genes that code for two different Na + -dependent cation-chloride cotransporter (CCC) paralogs. Aedes aegypti aeNKCC1 is an ortholog of Drosophila melanogaster Ncc69, a bumetanide-sensitive Na + -K + -2Cl - cotransporter (NKCC). Aedes aegypti aeCCC2 and aeCCC3 are orthologs of Drosophila Ncc83. Prior work suggests that the transport properties of aeCCC2 differ from canonical NKCCs. In particular, Xenopus oocytes expressing aeCCC2 have increased Na + -dependent membrane currents compared to controls, whereas NKCCs are electroneutral. Here, we further evaluated the function and localization of aeCCC2 and Ncc83. In oocytes expressing aeCCC2 or Ncc83, membrane potential (Vm ) hyperpolarized upon Na + removal; following hypotonic exposure the change in Vm was greater than it was in controls. In voltage-clamp experiments, membrane currents were concentration dependent on Na + with an apparent affinity (Km ) of approximately 4.6 mM. In Malpighian tubules of larval and adult mosquitoes, aeCCC2 was localized along the basolateral aspect of principal cells. Sequence comparisons among transporters from Drosophila, Aedes, Anopheles, and Culex revealed 33 residues within the transmembrane domains (TMDs) that are fully conserved within paralogs but that differ between orthologs of NKCC1 and orthologs of aeCCC2/Ncc83. These residues are distributed across all 12 TMDs. Our results provide a foundation for further exploration of the structural basis for functional differences between insect Na + -dependent CCCs. Graphical abstract: Image 1 Highlights: Ncc83 and aeCCC2 are members of the cation-chloride cotransporter (CCC) family. Oocytes expressing Ncc83 and aeCCC2 have increased sodium currents after swelling. Antibodies against aeCCC2 stain the basolateral aspect of mosquito renal tubules. Conserved sequence differences distinguish aeCCC2 and Ncc83 from other CCCs.